2016
DOI: 10.1073/pnas.1613744113
|View full text |Cite
|
Sign up to set email alerts
|

Structural and functional significance of water permeation through cotransporters

Abstract: Membrane transporters, in addition to their major role as specific carriers for ions and small molecules, can also behave as water channels. However, neither the location of the water pathway in the protein nor their functional importance is known. Here, we map the pathway for water and urea through the intestinal sodium/glucose cotransporter SGLT1. Molecular dynamics simulations using the atomic structure of the bacterial transporter vSGLT suggest that water permeates the same path as Na + and sugar. On a str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
34
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(37 citation statements)
references
References 35 publications
2
34
0
Order By: Relevance
“…This result is consistent with SUR1 providing four additional AQP4 binding sites in the SUR1-TRPM4 channel versus the TRPM4 channel ( Figure 9). Notably, the close apposition of SUR1-TRPM4 and AQP4 is similar to the arrangement of ion and water channels observed in water co-transporters (MacAulay et al, 2004;Zeuthen et al, 2016). Structural studies are currently underway to examine the proposed model in Figure 9.…”
Section: Functional Role Of the Sur1-trpm4-aqp4 Complexmentioning
confidence: 71%
See 1 more Smart Citation
“…This result is consistent with SUR1 providing four additional AQP4 binding sites in the SUR1-TRPM4 channel versus the TRPM4 channel ( Figure 9). Notably, the close apposition of SUR1-TRPM4 and AQP4 is similar to the arrangement of ion and water channels observed in water co-transporters (MacAulay et al, 2004;Zeuthen et al, 2016). Structural studies are currently underway to examine the proposed model in Figure 9.…”
Section: Functional Role Of the Sur1-trpm4-aqp4 Complexmentioning
confidence: 71%
“…In these "water co-transporters", osmolyte influx is immediately translated to water influx via the generation of small localized osmotic pressures (Duquette, Bissonnette, & Lapointe, 2001;Lapointe, Gagnon, Poirier, & Bissonnette, 2002). Water cotransporters are highly efficient, mediating 65% of intestinal water uptake (Zeuthen, Gorraitz, Her, Wright, & Loo, 2016), and have been shown to be associated with the majority of perisynaptic glutamate clearance (MacAulay, Hamann, & Zeuthen, 2004). Interestingly, certain water co-transporters, including the Na 1 /K 1 /2Clco-transporter-1 and volume-regulated anion channels, mediate cell volume changes in astrocytes (Nilius, 2004;Kimelberg, Macvicar, & Sontheimer, 2006;Jayakumar and Norenberg, 2010;Zeuthen, 2010).…”
mentioning
confidence: 99%
“…In recent years, it was shown that the SGLT1 behaves as a water channel . The passive SGLT1‐mediated water transport was independent of the presence of ligands, such as Na + and glucose, but the addition of glucose increased the transport of water into the cell and the rate of sugar‐coupled water transport was directly proportional to the rate of Na + /glucose cotransport.…”
Section: Discussionmentioning
confidence: 99%
“…Also here there is a significant absorption of water, and in the proximal fragment this process is more intense than in the rest of the intestine [3,10]. The absorption of water accompanies the transport of monosaccharides (mainly glucose) [4] and amino acids [3,11]. Water absorption in the gut can be of different nature: the transport of water together with the ions, the absorption of water by osmotic pressure of chyme, influenced by various humoral factors or changes in the functional state.…”
Section: Discussionmentioning
confidence: 99%
“…Experimental studies of processes in biological systems typically involve the evaluation of various concentrations of liquid components [1][2][3][4]. Changing of the concentration of these components can occur not only due to the transformation and movement of solutes, but also due to the change of the volume of the solvent.…”
Section: Introductionmentioning
confidence: 99%